Acquisition or strategic alliance? The Chinese telecommunication equipment manufacturers’ internationalization strategy choice in developed markets - Ning, Ziqi (2016)
After twenty years’ foreign exploration, Chinese telecommunication equipment manufacturing industry has achieved remarkable performance with a high level of internationalization. In fact, the achievement of MNEs in international business is determined largely by its internationalization strategy. And given the disadvantage of lacking ownership advantage inherently, emerging Chinese MNEs continuously conduct OFDI by acquisitions or alliances in developed markets. Therefore, the dissertation takes Huawei as a case to explore its strategy choice between acquisitions and strategic alliances in developed nations and tries to find out the drives behind Huawei’s choice.